Through the looking-glass, and what Alice found there - Carroll, Lewis, 1832-1898; Tenniel, Sir John (New York, NY : Scholastic Inc., 2016)
After climbing through the mirror in her room, Alice enters a world similar to a chess board where she experiences many curious adventures with its fantastic inhabitants.
Reading level: Grade 5.
Appeals to: 4th-th Graders.
Keywords: Fantasy